Effects of insecticide and acaricide mixtures on diaphorina citri control - Vechia, Jaqueline Franciosi Della [UNESP]; Junior de Andrade, Daniel [UNESP]; de Azevedo, Rafael Gomes [UNESP]; Ferreira, Marcelo da Costa [UNESP] (FapUNIFESP (SciELO), 2019)
-Pesticide mixtures are commonly used to reduce production costs in agriculture. However, the consequences of such practice towards target organisms are still unknown in most cases. Therefore, this study aimed to evaluate the effects of combinations of insecticides and one worldwide used acaricide on the control of Diaphorina citri (Asian citrus psyllid). All insecticides alone (lambda-cyhalothrin+thiamethoxam, phosmet, and imidacloprid) and in combination with spirodiclofen were efficient in controlling D. citri (> 80%). No significant effects were found for combinations of lambda-cyhalothrin+thiamethoxam and phosmet insecticides with spirodiclofen. Conversely, imidacloprid caused an antagonistic effect on the control of D. citri when mixed with the acaricide. After all, spirodiclofen had no effect on the pH and electrical conductivity of insecticidal spray solutions. Spirodiclofen mixtures with lambda-cyhalothrin+thiamethoxam and phosmet had no effect on D. citri control, but combinations with imidacloprid interfered with it.
Efeito da mistura de inseticidas e acaricida no controle de diaphorina citri
Keywords: Antagonist effect; Asian citrus psyllid; Citrus leprosis; HLB; Huanglongbing; Tank mixture